2019
DOI: 10.5194/pb-6-7-2019
|View full text |Cite
|
Sign up to set email alerts
|

Is Colobus guereza gallarum a valid endemic Ethiopian taxon?

Abstract: Abstract. Black-and-white colobus (Colobus guereza Rüppell, 1835) are arboreal Old World monkeys inhabiting large parts of the deciduous and evergreen forests of sub-Saharan Africa. Two of the eight subspecies of Colobus guereza are endemic to Ethiopia: C. g. gallarum and C. g. guereza. However, the validity of the Ethiopian taxa is debated and observed morphological differences were attributed to clinal variation within C. g. guereza. To date, no molecular phylogeny of the Ethiopian guerezas is available to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The potential importance of drift in African colobine skull evolution is consistent with their evolutionary history occupying forest patches that probably decreased in size with climatic cooling, reducing gene flow between groups and promoting stochastic evolutionary processes in allopatry 29 , 30 . In particular, the complexity of red colobus ( Piliocolobus ) taxonomy (reviewed in 55 ), the probable presence of a “hybrid swarm” of some taxa 56 , and the difficulties of assigning clear morphological boundaries between taxa 57 suggests an evolutionary history that is far from straightforward.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The potential importance of drift in African colobine skull evolution is consistent with their evolutionary history occupying forest patches that probably decreased in size with climatic cooling, reducing gene flow between groups and promoting stochastic evolutionary processes in allopatry 29 , 30 . In particular, the complexity of red colobus ( Piliocolobus ) taxonomy (reviewed in 55 ), the probable presence of a “hybrid swarm” of some taxa 56 , and the difficulties of assigning clear morphological boundaries between taxa 57 suggests an evolutionary history that is far from straightforward.…”
Section: Discussionmentioning
confidence: 58%
“…It has been hypothesised (e.g., 29 , 30 ) that climatic fluctuations in the Plio-Pleistocene shaped some of the taxonomic diversity of Afro-Eurasian monkeys, through expansion and contraction of suitable habitats. These habitat pockets may be equivalent to isolates, with little gene flow with other populations 31 .…”
Section: Introductionmentioning
confidence: 99%
“…do not share the tail characters of C. guereza gallarum (Carpaneto & Gippoliti 1994), so distribution of C. guereza gallarum appears limited to the Eastern Arusi and Chercher region (Groves 2007). A genetic study (Zinner et al 2019) has recently confirmed the validity of C. guereza gallarum and its restricted geographic range. This case offers another example of the practical importance of taxonomic knowledge for both basic research and conservation (Gippoliti 2019).…”
Section: Colobus Illiger 1811mentioning
confidence: 86%
“…e number of plant species consumed by guerezas in our study was much higher than that in Mekonnen and Hailemariam [17] (19 species), Hussen and Ejigu [18] (15 species), and Petros et al [47] (8 species). A higher number of different plant species consumed is expected in the dry season, as plants are of lower nutritional quality and so colobus monkeys would have to forage from a greater variety to meet their nutritional needs [48].…”
Section: Discussionmentioning
confidence: 99%